Hasrat dalam Iklan Permen Mentos ‘Say Freeze’ Menggunakan Pendekatan Semiotika Indeks, Ikon, dan Simbol - Michelia Aisha Rangkuti; Guruh Ramdani; Muhammad Farhan Aufar; Balqis Nabilah; Nayyara Alya Fazila (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study analyzes how visual signifiers in the Mentos Cool Gel “Say Freeze” advertisement construct and evoke consumer desire. The objective is to provide an understanding of how visual elements in advertising are strategically constructed to create seductive associations of meaning, which ultimately fail to offer full satisfaction. This research employs a qualitative descriptive method using Charles Sanders Peirce’s semiotic theory—particularly the categories of index, icon, and symbol—and Jacques Lacan’s theory of desire, supported by a literature review. The findings indicate that the Mentos “Say Freeze” advertisement employs a variety of visual elements to generate a chilling sensation that stimulates consumer desire, rather than simply promoting a candy product. These elements evoke fantasies of unattainable pleasure through the use of novelty and idealized identity images aligned with social norms. The advertisement also utilizes cross-sensory perception by replacing the sense of taste with visual cues. Critically, the ad manipulates desire, exploits psychological lack, and reinforces consumerist ideology by sacrificing individual authenticity and autonomy for capitalist gain. Therefore, this study emphasizes the need for ethical reflection on advertising practices.